(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The main aim of this study was to investigate the influence of culture on performance of different stakeholders in Sub Saharan Africa in international trade. The key guiding questions of this article were “How do cultural differences impact on international business in Sub Saharan Africa?” and “What are the main cultural issues an international business should consider”. Literature review was used as a method of collecting data. The key findings were that in Sub Saharan Africans have cultural attitudes classified as Polychronic. For, they do many things at once and their concept of time is free-flowing, and changes depending on each situation which adversely impact on their international business dealing. The conclusions were that, for participants in international trade in Sub Saharan Africa to have fair deals and progress international business they need to have cultural intelligence, be reasonably vigilant and enthused to attain an acceptable level of bargaining. and make a fundamental shift from the cultural orientation (Polychronic cultures); which is adverse from the view of international business.